Efforts And Strategies For Implementing Policies To Combat Begging In Cirebon City - Silviyatun Kasanah; Ipik Permana (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
Despite Cirebon City Regional Regulation No. 13 of 2019, which regulates public order and public safety, beggars still exist in public spaces in Cirebon City, particularly around the traffic lights of Kanggraksan, Rajawali, and Jabang Bayi. This indicates a discrepancy between policy formulation and implementation in the field. This study aims to examine the efforts and strategies used to implement the begging policy in Cirebon City and identify factors that influence its success. This study was conducted using a qualitative approach and case studies. By involving the Social Service, Public Order Agency (Satpol PP), beggars, and the surrounding community, data were collected through field observations, interviews, and documents. Data were analyzed descriptively, referring to George C. Edwards III's 1980 policy implementation model, which includes communication, resources, implementer attitudes, and bureaucratic structure. The study shows that policy implementation has not been fully implemented, primarily due to a lack of resources, poor communication of the policy to the public, and a lack of ongoing policy evaluation. Policy implementers, on the other hand, demonstrated a supportive attitude and sufficient commitment. This study shows that stronger, integrated, and sustainable implementation policies that focus on social empowerment are needed to address begging in Cirebon City.